Effects of perceived cost, service quality, and customer satisfaction on health insurance service continuance. Issue 4 (December 2017) - Abu-Salim, Taghreed; Onyia, Okey; Harrison, Tina; Lindsay, Valerie
Abstract This paper aims to contribute to the universal discourse on financial services continuance behavior by examining the impact ofservice cost on customers' service-quality perception and service continuance intention. It presents the results of an empirical study that has explored the impacts of service cost, service quality, and customer satisfaction on health insurance customers' behavioral intention toward continuing or discontinuing with their service providers. Very few studies had examined the impact ofservice cost onservice -quality perception . Our study attempts to fill that gap. A sample of 820 customers was surveyed, and 624 usable responses were analyzed with ANOVA, standard multiple regression, and logistic regression. Our findings indicate that, although highly satisfied health insurance customers will most likely retain their current service providers, customer dissatisfaction does not necessarily lead to discontinuance. Our results also provide some operational implications for health insurance managers, with strategies for reducing attrition and improving customer retention.